Histomorphological study of lichenoid dermatitides – A retrospective study - Selvam, Kalaivani; Bharathi Pradeep,; Jadhav, Chaithra; Udayashankar Carounanidy, (Asian Journal of Medical Sciences, 2023)
Background: Lichenoid dermatitis is a very common dermatological condition and is defined by features of basal cell damage and a dense band-like infiltration at the dermo-epidermal junction. There is a wide range of lesions included under this and the prototype lesion is Lichen Planus. Aims and Objectives: The aims of this study were to study the histopathological spectrum of the conditions with lichenoid tissue reaction and to find clinicopathological concordance of the lichenoid lesions. Materials and Methods: A retrospective study was conducted in a tertiary care center, where all the skin biopsy cases diagnosed clinically and/or histologically as lichenoid dermatitis for 2 years (2018–2019) were included in the study. Demographic details, clinical diagnosis, histological diagnosis, and the different histological features were collected from the respective case sheets and biopsy reports and entered in an excel worksheet. Frequency and percentages were used to represent the data. Results: A total of 47 cases were clinically diagnosed as lichenoid dermatitis, of which 38 cases showed concordance between clinical and histopathological diagnosis. Nine cases showed discordance between clinical and histopathological diagnosis and were categorized as lesions without lichenoid features. Seven cases were diagnosed as lichenoid dermatitis only on the histopathological study with an absence of such a differential diagnosis clinically. Out of the total 45 cases diagnosed as lichenoid dermatitis, 27 were lichen planus, five were lichen planus pigmentosus, four were hypertrophic lichen planus, three were lichenoid dermatitis, and two cases each of lichen planopilaris, lichen keratosis, and lichen sclerosis. Lichenoid dermatitis was seen commonly among the 41–50 years age group. Females were more commonly affected than males. Conclusion: Lichen planus is the prototype lesion among the lichenoid dermatitides. Definitive diagnosis of the specific entity among the lichenoid lesions is important as decision-making regarding the treatment modality and prognosis of the patient depends on it. Histopathological examination is vital for the definitive diagnosis, along with clinical correlation which concludes that clinicopathological correlation is the key.